Analisis peranan dompet dhuafa dalam mengentaskan kemiskinan bagi pedagang tangguh di kota balikpapan (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Shiva Aulia. 2019. Analysis of Dompet Dhuafas Role in Alleviating Poverty Through Pedagang Tangguh in Balikpapan City (study at Dompet Dhuafa Kaltim) supervised by Mr. Adi Wijaya and Mr. Agus Junaidi. The purpose of this research is to knew the role of Dompet Dhuafa Kaltim in alleviating poverty in Balikpapan City through the program of pedagang tangguh. In this research, alleviating poverty means alleviating the poverty which focus on receivers of pedagang tangguh program. The sample of this research are the receivers of pedagang tangguh program who are resided in Balikpapan City. The type of this research is used descriptive qualitative research. The method of collecting information in this research is done by literature study and field study. Field study in this research is done by interviewing The Chief of Dompet Dhuafa Kaltim, the person in charge of pedagang tangguh program and the receivers of pedagang tangguh program. The analytical technique which is used in this research is triangulasi technique. Dompet Dhuafa kaltim used minimum wage of Balikpapan City as an indicator of success from alleviating poverty. The result of the analysis shows that Dompet Dhuafa Kaltim has succeeded to alleviate the poverty of pedagang tangguh program receivers which is indicated by an increase of income with monthly income exceeding minimum wage of Balikpapan City.